Whiskey Tango Foxtrot - Shafer, David (Mulholland Books/Little, Brown & Company, 2014)
The Committee, an international cabal of industrialists and media barons, is on the verge of privatizing all information. Dear Diary, an idealistic online Underground, stands in the way of that takeover, using radical politics, classic spycraft, and technology that makes Big Data look like dial-up. Into this secret battle stumbles an unlikely trio: Leila Majnoun, a disillusioned non-profit worker; Leo Crane, an unhinged trustafarian; and Mark Deveraux, a phony self-betterment guru who works for the Committee. Leo and Mark were best friends in college, but early adulthood has set them on diverging paths. Growing increasingly disdainful of Mark's platitudes, Leo publishes a withering takedown of his ideas online. But the Committee is reading--and erasing--Leo's words. On the other side of the world, Leila's discoveries about the Committee's far-reaching ambitions threaten to ruin those who are closest to her.